Edukasi Tekhnik Penyajian ASI Perah Pada Karyawan Pabrik Indofood Di Wilayah Kota Makassar - Sumarni Sumarni; Nahira Nahira (Lembaga Pengembangan Kinerja Dosen, 2023)
Mother's milk is the best source of nutrition that can improve the health of mothers and children. Breastfeeding for babies is very important, especially in the early period of life, therefore it is enough for babies to be exclusively breastfed for the first 6 months without adding or replacing it with other foods or drinks . Working mothers are one of the reasons for not giving exclusive breastfeeding. After the maternity leave is over, many working mothers provide their babies with formula milk. One of the solutions that can be given is express breastfeeding to working mothers so that they can continue to provide exclusive breastfeeding. Expressing breast milk is one of the success factors of exclusive breastfeeding. Working mothers who have skills in expressing and storing breast milk will be more successful . This Community Service activity was carried out at the Indofood Factory in the Makassar City Region with a sample of Breastfeeding Mothers. Paired Samples Test was performed The results obtained were that there was an increase in knowledge from the average value of the pre-test questionnaire, the correct answer value was 6.8 after counseling was changed to 8.0 with a value of ρ = 0.000 which means there was an increase in understanding knowledge, benefits and how to do milking techniques, how to store and serve breast milk Milking the baby as well as knowledge about how to care for the breast.